THE DETERMINANTS OF TIMELINESS SUBMISSION OF FINANCIAL STATEMENTS IN THE COVID-19 ERA - Estevania, Catherine; Setijaningsih, Herlin Tundjung (International Journal of Application on Economics and Business, 2023)
This research aims to analyze whether profitability, auditor switching, liquidity, and company’s age affect timeliness submission of financial statements on basic material sector companies listed on the Indonesia Stock Exchange (IDX) during 2019-2021. Sample was selected using purposive sampling method and the valid data was 65 companies. Data processing technique using logistic regression analysis with a significance level of 5% which is assisted by SPSS 26 program and Microsoft Excel 2016. The results of this research indicate that auditor switching has an effect on timeliness submission of financial statements, while profitability, liquidity, and company’s age have no effect on timeliness submission of financial statements. The implication of this research is the need to change auditors to improve timeliness submission of financial statements to maintain the relevance of the information submitted.